2019
DOI: 10.1111/evo.13717
|View full text |Cite
|
Sign up to set email alerts
|

The evolution of eye size in response to increased fish predation in Daphnia

Abstract: Variation in eye size is ubiquitous across taxa. Increased eye size is correlated with improved vision and increased fitness via shifts in behavior. Tests of the drivers of eye size evolution have focused on macroevolutionary studies evaluating the importance of light availability. Predator‐induced mortality has recently been identified as a potential driver of eye size variation. Here, we tested the influence of increased predation by the fish predator, the alewife (Alosa pseudoharengus) on eye size evolution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 53 publications
0
22
0
Order By: Relevance
“…Given that the induction of TGP is dependent upon the ability of organisms to accurately receive information from environmental signals, it follows logically that components of the sensory system may also respond to environmental signals to ultimately enhance organismal performance. Yet, the link between the environment and transgenerational responses in sensory systems is largely unexplored [17].…”
Section: Introductionmentioning
confidence: 99%
“…Given that the induction of TGP is dependent upon the ability of organisms to accurately receive information from environmental signals, it follows logically that components of the sensory system may also respond to environmental signals to ultimately enhance organismal performance. Yet, the link between the environment and transgenerational responses in sensory systems is largely unexplored [17].…”
Section: Introductionmentioning
confidence: 99%
“…Evolutionary shifts in eye size have also been linked to changes in ecological conditions. For example, studies have quantified selection on eye size due to such factors as light availability (Hall, 2008; Hiller‐Adams & Case, 1988; Kröger & Fernald, 1994; Veilleux & Lewis, 2011), predation (Glazier & Deptola, 2011; Møller & Erritzøe, 2010; Nilsson et al., 2012), and competition (Beston et al., 2017, 2019; Beston & Walsh, 2019). This growing body of work illustrating similar shifts in brain and eye size in response to ecologically mediated selection foreshadows the possibility that selection favors coordinated shifts in these neurosensory systems.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, studies have shown that ecological factors such as habitat complexity, foraging, diel activity and predation are associated with evolved differences in eye size (Banks, Sprague, Schmoll, Parnell, & Love, ; Beston, Dudycha, Post, & Walsh, in press; Beston, Wostl, & Walsh, ; Brandon, James, & Dudycha, ; Caves et al, ; Glazier & Deptola, ; Hammerschlag et al, ; Thomas et al, , ; Veilleux & Kirk, ; Zaret & Kerfoot, ). Although such studies provide information on the relationship between eye size and the environment, the vast majority of this work has compared eye size across species (but see Beston, Wostl, et al, ; Beston et al, in press; Brandon et al, ; Lönnstedt, McCormick, & Chivers, ). Despite years of research, very little work has experimentally tested how natural selection shapes the evolution of complex traits, such as the vertebrate eye.…”
Section: Introductionmentioning
confidence: 99%